Inhibiton of green okra fruit (Abelmochus esculentus) extract against Staphylococus aureus ATCC 6538 root canals of teeth: Daya hambat ekstrak buah okra hijau (Abelmochus esculentus) terhadap Staphylococus aureus ATCC 6538 saluran akar gigi - Oktavia Nur Vitasari; Raditya Nugroho; Sri Lestari (Makassar Dental Journal PDGI Makassar, 2022)
Staphylococcus aureus is bacteria identified in the root canal of infected teeth by 20%, resistant and isolated from secondary root canal treatment. NaOCl 2.5%has toxic properties and causes irritation when pushed into periapical tissue. Green okra fruit (GOF) extract has antibacterial secondary metabolite compound i.e.flavonoids, alkaloids, saponins, tannins and terpenoids. This research was carried out to determine inhibition of GOF extract against S.aureus. Inhibition test useddisc diffution method which consisted of 5 research groups, i.e. GOF with concentration of 1.563%, 3.125%, 6.25%, and 12.5%, and 2.5% NaOCl; the ave-rage diameter of the inhibition zone of the concentration of GOF extract were 0 mm, 0 mm, 14.51 mm, 17.95 mm, and 24.56 mm, respectively. It was concluded that GOF extract has inhibition against of S.aureus starting from concentration of 6.25%. Green okra fruit extract has inhibition close to NaOCl 2.5% against S.aureus at concentration of 12.5%.